Efficacy of third-line chemotherapy following nanoliposomal irinotecan combined with fluorouracil and folinic acid as second-line treatment for unresectable pancreatic cancer - Miwa, Keisuke; Kawasaki, Reina; Shimokawa, Mototsugu; Otsuka, Taiga; Tanaka, Toshimitsu; Fukahori, Masaru; Shibuki, Taro; Nakazawa, Junichi; Arima, Shiho; Koga, Futa; Ueda, Yujiro; Kubotsu, Yoshihito; et al. (Frontiers in Oncology, 2025)
IntroductionThe significance of third-line chemotherapy (CTx) in unresectable pancreatic cancer (UPC) remains unclear. This study evaluated the therapeutic impact of third-line CTx after nanoliposomal irinotecan and fluorouracil combined with folinic acid (nal-IRI + 5-FU/LV) therapy as second-line CTx for UPC.MethodsBetween June 2020 and May 2021, 104 patients who received nal-IRI + 5-FU/LV therapy as second-line CTx were retrospectively analyzed for post-discontinuation survival (PDS) and overall survival (OS). Comparisons were made between patients transitioning to third-line CTx and those receiving best supportive care (BSC), using a Cox proportional hazards model adjusted for patient background.ResultsOf the cohort, 34 patients received third-line CTx, whereas 61 transitioned to BSC. The median OS from first-line CTx in the third-line CTx group was 18.0 months, with a median OS of 9.7 months from second-line CTx. Adjusted median PDS following second-line CTx was 6.5 months for the third-line CTx group compared to 2.3 months for the BSC group (adjusted hazard ratio 0.16; 95% confidence interval 0.08–0.32; P < 0.01).ConclusionThird-line CTx should be actively considered for patients with UPC, as the approach may significantly extend survival in those who can tolerate the treatment.